Wino-Higgsino dark matter in MSSM from the g − 2 anomaly - Sho Iwamoto; Tsutomu T. Yanagida; Norimi Yokozaki (Physics Letters B, 2021)
In this letter, we show that the wino-Higgsino dark matter (DM) is detectable in near future DM direct detection experiments for almost all consistent parameter space in the spontaneously broken supergravity (SUGRA) if the muon g−2 anomaly is explained by the wino-Higgsino loop diagrams. We also point out that the present and future LHC experiments can exclude or confirm this SUGRA explanation of the observed muon g−2 anomaly.